Green Human Resource Management and its Strategic Importance in the Modern Era: A Review and Research Framework - Muhammad Umar Shahzad (IJEBD (International Journal of Entrepreneurship and Business Development), 2020)
Sustainability is a buzz word in this 21st century where not just the nations but the organizations are trying to achieve the sustainable development goals set forth by United Nation Organization (UNO). Green HRM (GHRM) as an organization level initiative of climate action is at times needed by the organizations as regulatory requirement. It is crucial to consider the gap between intended and implemented HRM practices as it can affect the performance in the organization Similar, research consideration is required for such an intended – implemented gap in GHRM which is a research gap in the literature of GHRM. This conceptual article emphasizes on aligning the intended – implemented gap on GHRM and proposes a new research framework for green HRM as a strategic advantage with the propositions to be validated by the future researchers. Green HRM is a source of strategic advantage and it requires a detailed review with updated literature on the current situation. Current study would fulfil this gap.